POSS-based hybrid biomaterials for tissue engineering and regenerative medicine - Mi Chen; Yidan Wang; Min Wang; Wenhao Zhou; Sen Yu; Bo Lei (Materials Today Bio)
Polyhedral oligomeric silsesquioxanes (POSS), as an organic-inorganic hybrid nanomaterial, have shown broad application prospects in biomedical field due to their unique rigid nano core structure and abundant modifiable functional groups. These characteristics make it an ideal platform for preparing POSS-based hybrid biomaterials (POSSHB) with controllable mechanical properties and tunable degradability. This article systematically elaborates on the preparation method, structural characteristics, and basic properties of POSSHB; The latest research progress of this type of material in the fields of bone and cartilage regeneration, wound repair, cardiovascular tissue engineering, nerve repair, dental restoration, ophthalmic treatment, and skeletal muscle regeneration is summarized, and the key role of POSSHB in tissue regeneration is deeply explored; Finally, future development directions and prospects are proposed in response to the limitations of current research.